Implementation of Regional Government Information Systems as Online Practices for Planning, Budgeting and Administration Processes - Ika Dewi Prasasti Latifah; Ayuning Budiati; Dwi Putranto Riau (Department of Public Administration, 2023)
This study aims to find out how the implementation of planning, budgeting and administration in Anambas Islands Regency using the Sistem Informasi Pemerintahan Daerah (SIPD) and how the system model is more optimal in terms. The method used in this study is a qualitative method that describes a management information system that conceptually, structure and development are appropriate and the input, process, output and feedback. The data collection technique used in this study was by interviews, observation, and documentation studies with respondents in Anambas Islands Regency who are directly related to SIPD in their daily work. The results of the research and data analysis describe that the implementation of SIPD in the planning, budgeting and administration processes in Anambas Islands Regency is not optimal yet. This can be seen from SIPD which is still difficult to access due to network constraints and human factors. Therefore, a strong commitment from all parties is needed to maximize the SIPD function which wants to integrate the implementation of planning, budgeting, and administration.